Research on Impact of Distributed Photovoltaic Generation on Voltage in Distribution Network - ZHAI Wenjie; LI Jianquan; WU Xiaoyun; GUAN Rende; CUI Jian (Kongzhi Yu Xinxi Jishu)
It will bring a lot of impacts when grid-connected distributed photovoltaic generation on distribution network. This paper describes the voltage profile in radial distribution network within distributed photovoltaic generation, conducts a study on the analytical methods and evaluation index of voltage fluctuations caused by the output power variation of distributed photovoltaic generation, as well as the impact of feeder voltage profile when distributed photovoltaic generation parallels on different locations. The simulation of distribution network grid-connected distributed photovoltaic generation was provided to demonstrate its operating characteristics.